Response of Turkish financial markets to negative interest rate announcements of the ECB - Gökhan Ş. Güneş; Sumru Öz (Koç University-TÜSİAD Economic Research Forum (ERF), 2016)
This paper examines the impact of negative interest rate announcements of the ECB on Turkish financial markets. Negative Interest Rate Policies (NIRP) are expected to affect emerging market and developing economies (EMDEs) through an increase in the inflow of capital searching for higher yields. The expectation for an increase in short-term capital inflows to an EMDE might have transmission channels to the whole economy similar to those of expansionary monetary policies, except for a sign change in case of the exchange rate channel. The rest of the transmission channels are portfolio, interest rate, and credit channels. The latter is excluded from the analysis since it takes time to realize. Accordingly, we analyze the impact of negative interest rate announcements of the ECB on EUR/TRY and USD/TRY exchange rates; 1-month and 3-month TRLibor rates; BIST 100 Index, as well as 2-year and 10-year bond returns using GARCH (1,1) model. The results show that the announcements significantly affect both the volatility of Turkey's financial indicators and their returns especially through interest rate and portfolio channels. The robustness of the results on volatility is tested by using an event study.
Keywords: E58; F30; G10; 330; NIRP; transmission channels; financial indicators; Turkey